2014
DOI: 10.1186/s12935-014-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-492 expression promotes the progression of hepatic cancer by targeting PTEN

Abstract: BackgroundAberrant microRNA (miRNA) expression plays an essential role in the pathogenesis of Hepatocellular Carcinoma (HCC). However, specific involvement of miRNAs in HCC remains incompletely understood. The aim of this study was to explore the relevant microRNAs involved in the development of HCC.MethodsMicroRNA microarray was used to screen for the differentially expressed miRNAs in cancerous tissue and adjacent non-cancerous control tissue from patients with HCC (n = 3). Quantitative PCR was subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…Although deregulation in miRNA expression is a well‐known phenomenon in cancer and during metastasis, the functional role of single candidate miRNAs is still under investigation. Only few recent reports have shed light onto the functional role of miR‐492 in certain types of cancers . In this project, we investigated the functional impact of miR‐492 on HB metastasis in vitro and deciphered the genetic cascade triggered by the miRNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although deregulation in miRNA expression is a well‐known phenomenon in cancer and during metastasis, the functional role of single candidate miRNAs is still under investigation. Only few recent reports have shed light onto the functional role of miR‐492 in certain types of cancers . In this project, we investigated the functional impact of miR‐492 on HB metastasis in vitro and deciphered the genetic cascade triggered by the miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For breast and prostate cancer, similar effects on proliferation and anchorage‐independent growth have been published. Strong effects based on repressing miR‐492 by siRNA in liver cancer cell lines may depend on blocking miR‐492 in combination with its host gene KRT19 . In this regard, overexpression of miR‐492 may deliver more specific data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies suggested that the transcriptional role of PTEN involves a key position in the complex network of tumor suppressor and oncogenes that regulate cellular transformation. PTEN downregulation was found in lung cancer (28), hepato cellular carcinoma (29), and prostate cancer (30). PTEN level might be related to the biology of Ewing's sarcoma cells and loss of PTEN could result in clinically more aggressive tumors (31).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular alteration Function Reference miR155-5p PTEN Upregulation Cellular proliferation and invasion (Fu et al, 2017) miR-494 PTEN Upregulation Cellular proliferation and invasion miR-519a PTEN Upregulation Cellular proliferation and invasion (Tu et al, 2016) miR-492 PTEN Upregulation Cellular proliferation and invasion (Jiang et al, 2014) miR-21 PTEN, hSulf-1 Upregulation Cellular proliferation and metastasis (Bao et al, 2013) miR-93 PTEN, CDKN1A Upregulation Cellular proliferation (Ohta et al, 2015) miR-222 PPP2R2A Upregulation Cellular proliferation (Wong et al, 2010) miR-3127 AKT, FOXO1 Upregulation Cellular proliferation Abbreviations: AKT, protein kinase B; miRNA, microRNA; mTOR, mammalian target of rapamycin; PI3K, phosphoinositide 3-kinase.…”
Section: Microrna Targetmentioning
confidence: 99%